The Shift in the Concept of Head of Family for Working Women: An Islamic and Gender Perspective in Pekanbaru - Alfiah; Fitrah Herlinda; Nur’aini Safitri; Nadya Azhari Rambe (Soshum: Jurnal Sosial dan Humaniora, 2025)
The role of women in the digital era has experienced a significant transformation, no longer limited to domestic responsibilities as housewives, but also extending to active participation in the professional sphere. An increasing number of women choose to pursue careers after marriage, which in some cases leads them to become the main breadwinners for their families. This phenomenon challenges the conventional view that men are the sole heads of families and opens discourse on the redefinition of family leadership. This study aims to explore the meaning of being the head of the family for working women in Pekanbaru who either act as the main financial provider or earn a higher income than their husbands. Employing a phenomenological approach, this research involved ten female informants who shared their lived experiences. Data were collected through in-depth interviews and analysed using Colaizi’s method to identify core themes. The findings reveal that there is a noticeable shift in the understanding of family headship among these women. For those who serve as the primary providers, the concept of “head of the family” is interpreted not merely as a legal or formal title, but as a functional and relational responsibility encompassing economic, emotional, and social dimensions. The meaning of leadership in the family is thus redefined through practical roles and cooperation between spouses rather than rigid gender hierarchy. This study concludes that the redefinition of family headship among working women in Pekanbaru reflects a contextual interpretation of Islamic values, where leadership in the household is viewed as a shared responsibility based on capability and contribution rather than gender alone.